2001
DOI: 10.1002/mus.1039
|View full text |Cite
|
Sign up to set email alerts
|

Gender, body mass and age as risk factors for ulnar mononeuropathy at the elbow

Abstract: Factors that predispose patients to ulnar mononeuropathy at the elbow (UME) are poorly defined. We compared 112 electrodiagnostic reports which met criteria for definite or probable UME to 104 reports which excluded UME. Male gender was strongly associated with definite (OR = 6.9, 95% CI = 2.4-20.4; P < 0.001) and all UME (OR = 2.2, 95% CI = 1.2-4.1; P = 0.010) after controlling for age and body mass index (BMI). Among men, UME was associated with increasing age (P = 0.008) but not a decreased BMI. Women, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 14 publications
9
57
4
3
Order By: Relevance
“…15,17 Richardson et al 17 suggested that external compression at the elbow is a more important cause of UNE among women than men. Matev 15 recently reported that, in men, the ulnar nerve is more mobile and therefore more sensitive to gliding impairment at the medial epicondyle.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 Richardson et al 17 suggested that external compression at the elbow is a more important cause of UNE among women than men. Matev 15 recently reported that, in men, the ulnar nerve is more mobile and therefore more sensitive to gliding impairment at the medial epicondyle.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how the observed prevalence may have changed with survey of a cohort more reflective of the whole U.S. population. Because previous studies have suggested male sex and occupational activities (e.g., manual labor jobs, repetitive elbow motion) to be risk factors for cubital tunnel syndrome, the underrepresentation of these groups in our cohort [27][28][29] may have led to a relative underestimation of disease burden in comparison with a true representative population. We enrolled 74% of subjects who started the survey.…”
mentioning
confidence: 92%
“…leaning one´s elbow on hard surfaces), may pre-dispose to UNE [2][3][4]. Gender, high body mass index (BMI), smoking and diabetes, have not consistently been found to increase the risk or being associated with UNE [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%